Democracy promotion and electoral quality: A disaggregated analysis. Issue 2 (13th August 2020) - Steele, Carie A.; Pemstein, Daniel; Meserve, Stephen A.
Abstract: The international community spends significant sums of money on democracy promotion, focusing especially on producing competitive and transparent electoral environments. In theory, aid empowers a variety of actors, increasing competition and government responsiveness. We argue that to fully understand the effect of aid on democratization one must consider how democracy aid affects specific country institutions. Building on theory from the democratization and democracy promotion literature, we specify more precise causal linkages between democracy assistance and elections. Specifically, we hypothesize about the effects of democracy aid on the implementation and quality of elections. Building on canonical work, we test these hypotheses, using V‐Dem's detailed elections measures to examine the impact of democracy aid. Intriguingly, we find that there is no consistent relationship between democracy and governance aid and the improvement of disaggregated indicators of election quality, but aggregate measures still capture a relationship. We suggest that current evidence is more consistent with election‐enhancing aid following democratization than with democratization following such aid.